2022
DOI: 10.21037/tp-21-516
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of phentolamine combined with ambroxol aerosol inhalation in the treatment of pediatric severe pneumonia and its effect on serum IL-10 and CRP levels

Abstract: Background:The aim of the present study was to determine the therapeutic effect of phentolamine combined with Ambroxol aerosol inhalation on pediatric severe pneumonia and its effect on serum interleukin-10 (IL-10) and C-reactive protein (CRP) levels.Methods: Eighty-five children with severe pneumonia treated in our hospital from November 2019 to November 2020 were selected as the research participants, and were divided into the routine group (n=41) and treatment group (n=44) according to odd and even admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Similarly, the results of Han et al [17] demonstrated that phentolamine significantly prevents acute kidney injury and reduces inflammation and apoptosis in mice. Previous studies have shown that phentolamine can significantly improve the inflammatory response and lung function in severe neonatal pneumonia [18]. This is the first time we have reported the inhibitory role of phentolamine on inflammation and apoptosis in embryonic lung cells.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, the results of Han et al [17] demonstrated that phentolamine significantly prevents acute kidney injury and reduces inflammation and apoptosis in mice. Previous studies have shown that phentolamine can significantly improve the inflammatory response and lung function in severe neonatal pneumonia [18]. This is the first time we have reported the inhibitory role of phentolamine on inflammation and apoptosis in embryonic lung cells.…”
Section: Discussionsupporting
confidence: 55%
“…These factors have limited its widespread use [ 30 , 31 ]. Phentolamine has been widely used in clinical practice, and a large number of studies and clinical data have confirmed its safety [ 32 ]. The current study is the first to describe its use as an antibacterial agent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment of CAG is particularly important. At present, the treatment of CAG in modern medicine mainly aims to improve the symptoms of patients by eradicating Hp infection, enhancing barrier function, and reducing bile reflux [ 17 , 18 , 19 ]. However, it has the disadvantage of a high recurrence rate.…”
Section: Classification Of Chronic Gastritismentioning
confidence: 99%